KINERJA KEUANGAN DAN NON KEUANGAN TERHADAP RETURN SAHAM SEKTOR PERBANKAN DI BEI 2018-2022: Financial and Non-Financial Performance on Stock Returns of the Banking Sector on the IDX 2018-2022 - Winda Sari; Yulia Setyarini (J-MACC, 2024)
This research was conducted with the aim of determining the influence of Capital, Assets, Earnings, Liquidity and CSR on stock returns in the IDX banking sector 2018-2022. Data used secondary data. Type of quantitative research on secondary data through financial reports. The population is 47 companies. The sample was selected based on Purposive Sampling so that 31 companies were found. The data was analyzed using SPSS data through a set of tests that support multiple regression analysis and hypothesis testing. The results of this research are: 1) There is an influence of company financial performance as measured by Capital on stock returns in the IDX banking sector 2018-2022. 2) There is an influence on the company's financial performance as measured by assets on stock returns in the IDX banking sector 2018-2022. 3). There is an influence on the company's financial performance as measured by Earnings on IDX banking sector stock returns 2018-2022. 4) There is no influence on the company's financial performance as measured by liquidity on stock returns in the IDX banking sector 2018-2022. 5) There is no influence on the company's non-financial performance as measured by Corporate Social Responsibility on returns in the IDX banking sector 2018-2022.